Penerapan Weighted Product Method (WPM) Pada Pemilihan Peserta DIKBANGUM Terbaik Polda Bengkulu - Elfianty, Lena (MEANS (Media Informasi Analisa dan Sistem), 2020)
To improve the quality of existing police resources, motivation must be given for achievement in participating in educational activities. The selection system was carried out both by the Bengkulu Regional Committee according to instructions and directions given by the National Police Headquarters. So that in accordance with the motto proclaimed by the National Police Headquarters namely Clean, Transparent, Accountable and Humanist. (Bersih, Transparan, Akuntabel dan Humanis). The selection system used is still using MicroSoft Excel as its assistance software, especially the acceptance of the Police Academy, Police and Private Officers. For other selections, it is also possible to use a special program created. Whereas the determination of the best DikBangUm participants will be better if it is processed using good management techniques and rules in the form of a decision support system (DSS) used by the Weighted Product Method (WPM) which is considered the most appropriate to be applied.